Pelaksanaan Model Pembelajaran Inovatif Berbasis Pendekatan Saintifik untuk Pembelajaran Bahasa Inggris di MTsN 1 Tanah Datar - Hidayatul Fitri; Suswati Hendriani; Sirajul Munir; Annisaul Khairat (ISLAMIKA, 2023)
The aims of this study were 1) to find out the planning of learning English with an innovative learning model based on a pendekatan saintifikat MTsN 1 Tanah Datar, 2) to find out the implementation of learning language with an innovative learning model based on a pendekatan saintifikat MTsN 1 Tanah Datar. This type of research is case study research with a qualitative approach. The research location is at MTsN 1 Tanah Datar. The research informants were 3 English teachers at MTsN 1 Tanah Datar. The research instruments were interview guides, observation sheets and documentary evidence. The data collection technique used is through in-depth interviews, participatory observation and documentation studies. The data analysis technique is by means of data triangulation. The results of the study include showing that 1) lesson planning is carried out by the English teacher in coordination with teachers of the same family, homeroom teachers, other subject teachers, representatives of the curriculum sector, representatives of the infrastructure sector and other related parties; 2) In the implementation stage, the English teachers at MTsN 1 Tanah Datar are in accordance with the learning implementation indicators.